Comparative Analysis of Real Time Systems in E- Commerce in Indonesia Post Covid-19 Era - Afif Badawi (Journal of International Conference Proceedings (JICP), 2022)
The purpose of this study is to compare systems and features in E-Commerce with a high real time level. This comparison must be made by determining which E-Commerce between QRIS (Quick Responses Code Indonesian Standard) and other online payments has the real time level expected by its users. Because if the real time level is not as expected by the user, the use of QRIS will not be achieved. This research was conducted by testing the usability testing of the use of QRIS compared to others. The results of the study illustrate that the use of QRIS has not been made every transaction in real time because there is a system that has not been completed. The conclusion in this study provides an overview of the weaknesses of the system and features in QRIS so that efforts are made to utilize and utilize QRIS. Thus, at the end of this study, Keywords: Comparative Analysis, Real Time Systems, Post Covid-19 Era, QRIS.